What are the risks and benefits of kangaroo mother care in preterm and low‐birth‐weight infants?. Issue 8 (August 2015) - Pickersgill, Angela; Mounsey, Anne
Abstract : Evidence‐Based Answer : "Kangaroo mother care" (KMC) or skin‐to‐skin care with nearly exclusive breastfeeding reduces morbidity, mortality, severe infection, nosocomial infection, hypothermia, and length of hospital stay in low‐birthweight (LBW) and preterm infants in low‐ to middleincome countries. No risks from KMC have been reported. However, in small and premature infants in high‐income countries, it appears to only promote continuation of some breastfeeding (SOR: B, systematic reviews and meta‐analyses of RCTs with some bias).